2013
DOI: 10.1021/am403609y
|View full text |Cite
|
Sign up to set email alerts
|

Single ZnO Microrod Ultraviolet Photodetector with High Photocurrent Gain

Abstract: An Ag/ZnO microrod/Ag ultraviolet photodetector is fabricated, the ZnO microrod shows a hexagonal whispering gallery cavity structure. Upon a 325 nm ultraviolet illumination, the device shows a high sensitivity of 4 × 10(4) A/W and a high photocurrent gain of 1.5 × 10(5) at 5 V bias. Under different illumination power P, the photocurrent Ilight obeys a power law relation Ilight ∝ P(0.69). The high performance is probably attributed to a Schottky barrier at Ag/ZnO interface and optical whispering gallery mode e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…Researchers have demonstrated that the photoresponse of ZnO photodetector can be improved by optical resonant cavity effect and multireflection processes in the micro/nano-structures. 9 The tin-doped CdS nanowires with hexagonal cross section have a typical whispering gallery mode microcavity structure. The light can be totally internal reflected on the inner wall and form a hexagonal closed optical loop.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that the photoresponse of ZnO photodetector can be improved by optical resonant cavity effect and multireflection processes in the micro/nano-structures. 9 The tin-doped CdS nanowires with hexagonal cross section have a typical whispering gallery mode microcavity structure. The light can be totally internal reflected on the inner wall and form a hexagonal closed optical loop.…”
Section: Resultsmentioning
confidence: 99%
“…4,8 Up to date, various 1D inorganic materials, such as ZnO, GaN, InAsSb, ZnS, Zn x Cd 1−x Se, ZnTe, CdS, In 2 Te 3 , InSe, have been used to fabrication photodetectors. 4,[9][10][11][12][13] It has been demonstrated that the photoresponse properties of these fabricated detectors are determined critically by a variety of parameters including contact type of device, selected material, as well as the crystalline quality, dimension, surface adsorption and doping. Cadmium sulfide (CdS), as an important semiconductor with direct band gap of 2.47 eV (∼503 nm) at room temperature, has demonstrated interesting physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal Evaporation [41] Ag/ZnO microrod/Ag Schottky contacts (20 mm) t r ¼ 6.28 t d ¼ 0.8 λ ¼ 325, P ¼ 24 9 Â 10 5 1.5 Â 10 5 4 Â 10 4 (5 V) Thermal Evaporation [38] Al/ZnO NW networks on ITO/Al (400 mm)…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the time constants of rise stage are t 1 ¼ 6.27 s and t 2 ¼ 37.1 s, and their relative weight factors are 85 and 15%, respectively, which give an average rise time constant of t r ¼ 11.02 s; the estimated time constants of the decay stage are t 1 ¼ 0.28 s and t 2 ¼ 6.85 s, with relative weight of 67 and 33%, respectively, producing an average decay time constant t d of 2.43 s. It was found that the rise process of NW array PD (1.38 s) is much faster than that of single NW PD (11.02 s), while the resetting process of ZnO NW array PD (4.05 s) is also comparable with that of single NW device (2.43 s). [6,9,11,14,16,19,20,22,25,27,[33][34][35][36][37][38][39][40][41][42] Compared to low temperature synthesized ZnO nanorods reported in reference, [35,36] ZnO NW arrays grown by CVD at high temperature have better crystal quality, which contributes to the high performance of our devices. Table 1 compares the photoresponse of different ZnO NW-based UV PDs as reported previously.…”
Section: Photoresponse Behavior Of Zno Nw Uv Pdsmentioning
confidence: 99%
See 1 more Smart Citation